2016
DOI: 10.1111/tgis.12209
|View full text |Cite
|
Sign up to set email alerts
|

Bringing GEOSS Services into Practice: A Capacity Building Resource on Spatial Data Infrastructures (SDI)

Abstract: Data discoverability, accessibility, and integration are frequent barriers for scientists and a major obstacle for favorable results on environmental research. To tackle this issue, the Group on Earth Observations (GEO) is leading the development of the Global Earth Observation System of Systems (GEOSS), a voluntary effort that connects Earth Observation resources world-wide, acting as a gateway between producers and users of environmental data. GEO recognizes the importance of capacity building and education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…For example, applying machine learning techniques can be valuable to enhance extraction of information and classification (Camps-Valls, 2009;Lary, Alavi, Gandomi, & Walker, 2016). Additionally, DC being a new promising technology, capacity building efforts should be considered to ensure both technology transfer and to enable users to become familiar with this technology and raise awareness on how this can be useful in leveraging the potential of EO data (Desconnets et al, 2017;Giuliani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, applying machine learning techniques can be valuable to enhance extraction of information and classification (Camps-Valls, 2009;Lary, Alavi, Gandomi, & Walker, 2016). Additionally, DC being a new promising technology, capacity building efforts should be considered to ensure both technology transfer and to enable users to become familiar with this technology and raise awareness on how this can be useful in leveraging the potential of EO data (Desconnets et al, 2017;Giuliani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As a general remark, the authors underline the fact that the QoS limits set for INSPIRE's download service are designed to serve data to generally support the formulation, implementation, monitoring and evaluation of policies and activities, which have a direct or indirect impact on the environment. In this regard, this research has demonstrated that istSOS is suitable for most of the scientific or operational applications where data are accessed by tens of users with peaks of one hundred in emergency cases [14,39]. However, it also demonstrated that its capacity of scaling with increasing size of monitoring network, either in term of number of stored observations or sensors, is limited.…”
Section: Discussionmentioning
confidence: 94%
“…In order to provide quality and timely data to inform evaluation and decision processes, existing Earth Observation infrastructures must be improved. Data sharing is explored in the Black Sea catchment with Geonode, which is an Open Source Geospatial Content Management System [18] and Bringing GEOSS services into practice capacity, which is a capacity-building material that aims at teaching how to configure, use, and deploy a set of open source software to set up a spatial data infrastructure (SDI) [19]. Once data are acquired and shared, it can be more easily processed.…”
Section: Limited Access To Datamentioning
confidence: 99%